2006
DOI: 10.1210/en.2006-0486
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Fatty Acid Synthase in Breast and Endometrial Cancer: An Alternative to Selective Estrogen Receptor Modulators?

Abstract: There is an urgent need to identify and develop a new generation of therapeutic agents and systemic therapies targeting the estradiol (E2)/estrogen receptor (ER) signaling in breast cancer. In this regard, new information on the mechanisms of E2/ER function and/or cross talk with other prosurvival cascades should provide the basis for the development of other ideal anti-E2 therapies with the intent to enhance clinical efficacy, reduce side effects or both. Our very recent assessment of the mechanisms by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 80 publications
4
92
0
4
Order By: Relevance
“…More than being a marker of PrlR I146L constitutive activity, phosphorylated STAT5 is a thus good candidate contributing to the pathogenesis of MFAs. The molecular pathways that could mediate its effects may involve FAS, as the latter was proposed to stimulate survival and proliferation of breast cancer cells via complex mechanisms interfering with ER actions (31). Similar mechanisms could also occur in MFA, in which ER expression was also assessed (not shown).…”
Section: Discussionmentioning
confidence: 96%
“…More than being a marker of PrlR I146L constitutive activity, phosphorylated STAT5 is a thus good candidate contributing to the pathogenesis of MFAs. The molecular pathways that could mediate its effects may involve FAS, as the latter was proposed to stimulate survival and proliferation of breast cancer cells via complex mechanisms interfering with ER actions (31). Similar mechanisms could also occur in MFA, in which ER expression was also assessed (not shown).…”
Section: Discussionmentioning
confidence: 96%
“…FASN is a complex multifunctional enzyme that plays a central role in endogenous lipogenesis in mammals [28,29] . It has been reported that the overexpression of FASN together with a high proliferative index of breast cancer cells are associated with a nine-fold increased risk of patient mortality [30] . Accordingly, we examined the level of FASN by comparing breast cancer cell lines with different proliferative capability.…”
Section: Discussionmentioning
confidence: 99%
“…Among the enzymes involved in lipid biosynthesis in tumor cells, the most studied is FAS, which is regulated by different growth factor signaling, including epidermal growth factor (EGF), as well as by steroid hormoneinduced transduction pathways, including estradiol (E2) and its cognate receptor (ER) [13,18]. Downstream of the growth factors and steroid receptors, the phosphatidylinositol-3-kinase (PI3K)/Akt, and mitogen-activated protein kinase (MAPK) signaling pathways have been suggested to mediate FAS expression through the sterol regulatory element-binding protein 1c (SREBP-1c) [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of the growth factors and steroid receptors, the phosphatidylinositol-3-kinase (PI3K)/Akt, and mitogen-activated protein kinase (MAPK) signaling pathways have been suggested to mediate FAS expression through the sterol regulatory element-binding protein 1c (SREBP-1c) [13,18]. However, the up-regulation of FAS by activated growth factor receptors requires a complex signaling network [19,20].…”
Section: Introductionmentioning
confidence: 99%